Nursing of a patient with pyopneumothorax and respiratory failure caused by pulmonary fungal infection after chemotherapy for esophageal cancer (1例食管癌化疗后肺真菌感染致脓气胸合并呼吸衰竭患者的护理体会) - LI Lin (李琳) (Association of Integrative Nursing, 2024)
To summarize the nursing process of a patient with pulmonary fungal infection complicated by pyopneumothorax and respiratory failure after chemotherapy for esophageal cancer. The key points of nursing included early identification of illness condition changes and improvement of risk prediction ability. On the basis of multi-disciplinary cooperation, care bundles including drainage tube monitoring and maintenance, oxygen therapy nursing, psychological nursing, diet nursing and so on were carried out. After more than 1 month of active treatment and professional nursing care, the patient recovered satisfactorily. (本文总结1例食管癌化疗后肺真菌感染致脓气胸合并呼吸衰竭患者的护理经验。早期识别病情变化, 提高风险预判能力; 在多学科协作的基础上落实引流管的观察与护理、氧疗护理、心理护理、饮食护理等集束化干预措施。通过开展精细化的治疗和护理, 促进患者早期康复, 提高其生存质量。)